Slope Reinforcement Design for Balikpapan-Samarinda Toll Road Landslide Section 28+000 To 28+100. - Fitri, Siti Nurlita; Diputra, Marbono Widya (Jurnal Teknik Sipil dan Perencanaan, 2023)
The Balikpapan - Samarinda Toll Road is a new infrastructure project that connects two capital cities in East Borneo. Landslides occur in sections 28+000 to 28+100, necessitating the terrace design to prevent unstable conditions. As a result, a new proposed design is required to ensure safety in this area. This study aims to offer further slope reinforcement in this location to prevent landslides. This research utilizes secondary data from Standard Penetration Test (SPT) results to determine the soil properties. First, the lateral earth pressure was conducted to calculate the sheet pile and retaining wall structure. The other reinforcement is geogrid with geotextile combine. The Finite element model carried out all the overall stability with Plaxis calculation. The results show that all new proposed to generate the safety factor value 1.3. Sheet pile variations present the CCSP type W-600 with a total length reaching 17m, which offers a safety factor 1.31. The second variation is a retaining wall with a full height of 5m and combined in sheet pile design, which reaches the safety factor in the overall stability of 1.498. the internal strength of the retaining wall is divided into three categories: overturning, sliding, and bearing capacity with 1.55, 2.44, and 2.88, respectively. Meanwhile, the geogrid type described the SF 1.32 with three step slope design and spacing of 0.3m, 0,5m, and 1,0m, respectively.